Prosthetic rehabilitation of anophthalmic ocular sinistra and phthisis bulbi ocular dextra: a case report - Susilo, Rivani; Damayanti, Lisda; Novianti, Vita Mulya Passa (Universitas Padjadjaran, 2025)
Introduction: Loss of an eyeball due to enucleation or phthisis bulbi results in functional deficiency and facial deformities. This condition can cause significant psychological distress, especially if it results from unexpected infections or trauma. Case Report: A 30-year-old male patient presented to the Prosthodontic Clinic at Universitas Padjadjaran's Dental Hospital with complaints of low self-confidence due to his eye condition. The patient lost his left eye in childhood due to trauma and subsequently underwent surgical removal. Examination revealed a healthy conjunctiva with no signs of infection. Meanwhile, the right eye had experienced an infection six years ago but had not been removed. Examination showed a shrunken eyeball with vision loss. Bilateral custom ocular prostheses were fabricated for aesthetic purposes. Disscusion: Maintaining a healthy socket condition, preserving the ability of eye muscles to blink, normal eyelash positioning, preventing superior or inferior eyelid malposition, and maintaining normal eyelid closure post-enucleation or phthisis bulbi are crucial factors for the creation of an ideal ocular prosthesis. This case report outlines socket rehabilitation in a case of anophthalmic ocular sinistra and phthisis bulbi ocular dextra, focusing on preserving socket shape and support from muscles. Conclusion: Precisely crafted ocular prostheses offer advantages in retention, stability, aesthetics, and comfort for patients with anophthalmic sockets following enucleation and phthisis bulbi.